2019
DOI: 10.1038/s41598-019-49919-y
|View full text |Cite
|
Sign up to set email alerts
|

Random transposon insertion in the Mycoplasma hominis minimal genome

Abstract: Mycoplasma hominis is an opportunistic human pathogen associated with genital and neonatal infections. Until this study, the lack of a reliable transformation method for the genetic manipulation of M. hominis hindered the investigation of the pathogenicity and the peculiar arginine-based metabolism of this bacterium. A genomic analysis of 20 different M. hominis strains revealed a number of putative restriction-modification systems in this species. Despite the presence of these systems, a reproducible polyethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…mycoides strain PG1 as the reference. This coding sequence was subsequently cloned in the plasmid pMT85 ( 43 , 56 61 ). The plasmid backbone carries a transposon derived from Tn 4001 ( 62 ), the insertion of which can be selected through the gentamicin resistance gene aacA-aphD placed under the control of its natural promoter.…”
Section: Resultsmentioning
confidence: 99%
“…mycoides strain PG1 as the reference. This coding sequence was subsequently cloned in the plasmid pMT85 ( 43 , 56 61 ). The plasmid backbone carries a transposon derived from Tn 4001 ( 62 ), the insertion of which can be selected through the gentamicin resistance gene aacA-aphD placed under the control of its natural promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Meygret et al also reported that there were no antimicrobial resistance genes associated with these reported MICE. In related research, minitransposons have been used, albeit artificially, to deliver tetracycline resistance genes (30). This is further backed by the frequent occurrence of HGT that occurs in mollicutes and prokaryotes in general (31,32) and the phenomenon's ability to confer antimicrobial resistance (27,33), as well as the presence of genes in the ICE region of M. hominis, such as the aforementioned serine recombinase and Tn916 integrase, and including ArdA, a known facilitator of gene mobility (34).…”
Section: Discussionmentioning
confidence: 99%
“…mycoides strain PG1 as reference. This coding sequence was subsequently cloned in the plasmid pMT85 (42,58,(70)(71)(72)(73)(74). The plasmid backbone carries a transposon derived from Tn4001 (75), the insertion of which can be selected through the gentamicin resistance gene aacA-aphD placed under the control of its natural promoter.…”
Section: Establishing a Polyvalent Meos32 Expression System For Palm In Multiple Mycoplasmasmentioning
confidence: 99%